Integrated policymaking choosing an institutional design for implementing the Sustainable Development Goals (SDGs) - Breuer, Anita; Leininger, Julia; Tosun, Jale (Discussion paper, 2019)
Implementing the 2030 Agenda in an integrated way poses new challenges to political institutions and processes. In order to exploit synergies and to mitigate trade-offs between the Sustainable Development Goals (SDGs), innovative governance approaches are needed. National bodies to coordinate SDG implementation were being created as of late 2015. As a basis for future analyses on effectiveness, it is important to know if, and which, institutional designs are in place to implement the SDGs and why they were chosen. Against this background, this Discussion Paper analyses how political factors influence institutional design choices when it comes to implementing the SDGs. The aim of this paper is twofold: First, it seeks to assess governments' proposals for institutional designs for SDG implementation at the national level and to identify patterns of institutional designs. It does so by analysing and coding the Voluntary National Reviews from 2016 and 2017 of 62 signatory states, including OECD and none-OECD countries from all world regions and income groups. Second, it aims to explain which political and socio-economic factors shaped these institutional designs. The empirical analysis shows that the majority of countries have opted for a design that promotes political support at the highest level and cross-sectoral, horizontal integration, but has significant shortcomings in terms of social inclusiveness and vertical coordination across different levels of government. When asking which determinants shape these patterns, our findings reveal that horizontal integration becomes more likely with higher socio-economic development. Moreover, we find that vertical integration and societal integration are interdependent and mutually enforcing. Based on our findings, we formulate policy recommendations regarding the institutional requirements for integrated SDG implementation.